Topflowdf - a simple gis based model to simulate debris-flow runout on the fan - Scheild, Christian; Rickenmann, Dieter (Italian journal of engineering geology and environment, 2011)
Typically runout prediction methods - either based on empirical or on dynamical approaches - are applied to delineate possible debris-flow inundation zones on the fan for hazard mapping purposes. However, several case studies indicate that empirical relations may be valid only for situations which are similar to those represented by the data used for their development, and that a more accurate description of the debris-flow depositional process requires dynamical parameters which are often not easily constrained. In this study we propose that the topography of the potential deposition area has a major influence in the runout of a debris flow. We combine a random based flow algorithm, generating a maximum simulation perimeter on the fan, with the simple dynamical approach of a constant discharge model to predict the maximum runout on the fan. The program called TopFlowDF simulates deposition zones, associated deposition heights and a spatial distribution of the maximum flow velocities. The GIS-based simulation model runs with high resolution (2.5 m x 2.5 m) digital elevation models, generated for example from LiDAR data, and is tested with debris-flow events from Switzerland and South Tyrol. The predicted runout patterns of TopFlowDF are further compared with the empirical runout prediction method TopRunDF.